Excessive folic acid supplementation in pregnant mice impairs insulin secretion and induces the expression of genes associated with fatty liver in their offspring - Yuri Kintaka; Nobuhiro Wada; Seiji Shioda; Sadako Nakamura; Yuko Yamazaki; Kazuki Mochizuki (Heliyon, 2020)
Objective: Previous human and animal studies have shown that excessive maternal intake of folic acid (FA) predisposes to impaired glucose tolerance in the offspring. However, the underlying mechanism is unknown. Therefore, we aimed to determine whether excessive supplementation with FA during pregnancy affects the glucose tolerance of mouse offspring. Research methods & procedures: Pregnant C57BL/6J mice were fed AIN93G diet containing either 2 mg [control group (CN)] or 40 mg [high FA group (HFA)] FA/kg diet throughout their pregnancies. On postnatal days (PD)22 and 50, fasting blood glucose was measured in the offspring of both groups, and an oral glucose tolerance test (OGTT) was performed on PD50. On PD53, tissues were collected, and the tissue masses, area of insulin expression in the pancreas, liver triglyceride content, and gene expression were determined. Results: The blood glucose concentrations at 60 and 120 min of the OGTT were higher in female HFA than CN offspring. The serum fasting and non-fasting insulin concentrations and the area of insulin expression in the pancreas were lower in HFA than CN offspring. The liver triglyceride content was higher in female, and tended to be higher in male (P < 0.05), HFA offspring than CN offspring (P < 0.05). The liver mRNA expression of fat synthesis genes, such as Pparγ2 (male and female) and Cidec (male), was higher in HFA than CN offspring (P < 0.05). Conclusion: Excessive maternal supplementation of FA in mice leads to lower insulin synthesis and an impairment in hepatic fat metabolism in the offspring.